2016 IEEE Symposium Series on Computational Intelligence (SSCI) 2016
DOI: 10.1109/ssci.2016.7850128
|View full text |Cite
|
Sign up to set email alerts
|

Air quality forecasting using neural networks

Abstract: In this thesis project, a special type of neural network: Extreme Learning Machine (ELM) is implemented to predict the air quality based on the air quality time series itself and the external meteorological records. A regularized version of ELM with linear components is chosen to be the main model for prediction. To take full advantage of this model, its hyper-parameters are studied and optimized. Then a set of variables is selected (or constructed) to maximize the performance of ELM, where two different varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Air Quality Forecasting using Neural Networks [35]: Zhao et al suggested to apply extreme learning machine-based approach to forecast air quality. The case study was Helsinki, and the data included hourly air quality data (nitric oxide (NO), O 3 , PM 10 , PM 2.5 ) and meteorological data (relative humidity, pressure, temperature, and wind).…”
Section: Group 1: Neural Network (Nn)mentioning
confidence: 99%
“…Air Quality Forecasting using Neural Networks [35]: Zhao et al suggested to apply extreme learning machine-based approach to forecast air quality. The case study was Helsinki, and the data included hourly air quality data (nitric oxide (NO), O 3 , PM 10 , PM 2.5 ) and meteorological data (relative humidity, pressure, temperature, and wind).…”
Section: Group 1: Neural Network (Nn)mentioning
confidence: 99%
“…As it has been proved that a three-layer neural network can compute any arbitrary function [32]- [34], NN is able to present the complicated changes in fine-grained scenario. However, without considering the physical characteristics of AQI, the NN model may overfit and perform worse on the test data than on the training data [18].…”
Section: B Neural Network Modelmentioning
confidence: 99%
“…However, they mainly focus on 2D area, and can hardly produce a 3D fine-grained map. Neural networks (NN) are also used for forecasting on the AQI distribution [18]- [21]. However, its performance in fine-gained area is not satisfied without considering the physical characteristic of real AQI distribution.…”
Section: B Motivations For Realtime Fine-grained Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar and Goyal 10 applied the principal component regression method to forecast short-term daily air-quality index for four seasons in India. Zhao et al 11 proposed a regularized version of an extreme learning machine for air-quality forecasting. Zhou et al 12 trained a multi-output support vector machine (M-SVM) model by using multi-task learning algorithm to capture nonlinear relations and share the correlation information across related tasks.…”
Section: Introductionmentioning
confidence: 99%